Therapy for Mycobacterium kansasii Infection: Beyond 2018 - DeStefano, Michelle S.; Shoen, Carolyn M.; Cynamon, Michael H. (Frontiers in Microbiology, 2018)
Abstract The current standard of care therapy for pulmonary Mycobacterium kansasii infection is isoniazid (300mg/day), rifampin (600mg/day), and ethambutol (15mg/kg/day) for 12 months after achieving sputum culture negativity. Rifampin is the key drug in this regimen. The contribution of isoniazid is unclear since its in vitro MICs against M. kansasii are near the peak achievable serum levels and more than 100-fold greater than the MICs for M. tuberculosis. Ethambutol likely decreases the emergence of rifampin resistant organisms. There are several new drug classes (e.g. quinolones, macrolides, nitroimidazoles, diarylquinolines, and clofazimine) that exhibit antimycobacterial activities against M. tuberculosis but have not yet been adequately studied against M. kansasii infections. The evaluation of in vitro activities of these agents as well as their study in new regimens in comparison to the standard of care regimen in mouse infection models should be accomplished in order to inform development of human clinical trials of new regimens in comparison to the current standard of care regimen. It is likely that shorter and more effective therapy is achievable with currently available drugs.